A review on enhanced biogas production from anaerobic digestion of lignocellulosic biomass by different enhancement techniques. (September 2019) - Kainthola, Jyoti; Kalamdhad, Ajay S.; Goud, Vaibhav V.
Highlights: The challenges in the anaerobic digestion of lignocellulosic waste. Management of agricultural residue in a sustainable manner. Operational parameters and suggestion for optimized biogas yield. Various inhibitory compounds affecting the anaerobic digestion process. Abstract: Anaerobic digestion of lignocellulosic biomass has gained huge attention in current years, especially for degrading agricultural waste (i.e. rice straw, wheat straw etc.). Challenges related to anaerobic digestion of agricultural waste are low biogas yield, poor buffering capacity, low quality end products and potential variability. These inadequacies are either because of low mass transfer (high solid contents, poor nutritional structure) or can be accredited to recalcitrant nature of agricultural residues. To overcome these challenges various techniques exists like pretreatment of feedstock, co-digestion with different substrate and inoculation efficiency have been considered to increase the performance of anaerobic process. This review includes the effect of these techniques on lignocellulosic degradation, synergistic interaction with high C/N ratio feedstock and improving the buffering capacity by inoculum ratio optimization. Furthermore, key parameters influencing the anaerobic digestion are included with proposed future study.